The Incidence and Short-term Outcomes of Acute Respiratory Illness with Cough in Children from a Socioeconomically Disadvantaged Urban Community in Australia: A Community-Based Prospective Cohort Study - Hall, Kerry K.; Chang, Anne B.; Anderson, Jennie; Arnold, Daniel; Goyal, Vikas; Dunbar, Melissa; Otim, Michael; O’Grady, Kerry-Ann F. (Frontiers in Pediatrics, 2017)
Background Acute respiratory illnesses with cough (ARIwC) are predominant causes of morbidity in Australian Indigenous children however data on disease burden in urban communities are scarce. This study aimed to determine the incidence of ARIwC, the predictors of recurrent (≥4 episodes) ARIwC and development of chronic cough following an ARIwC in urban, predominantly Indigenous, children aged <5 years from northern Brisbane, Australia. Methods Prospective cohort study of children aged <5 years registered with a primary healthcare center. ARIwC episodes and outcomes were collected for 12 months. Recurrent ARIwC was defined as ≥4 episodes in 12 months. Chronic cough was defined as cough lasting > 4 weeks. Children who developed chronic cough were reviewed by a pediatric pulmonologist. Incidence densities per child-month of observation were calculated and predictors of recurrent ARIwC and chronic cough were evaluated in logistic regression models. Results Between February 2013 and November 2015, 200 children were enrolled; median age of 18.1 months, range (0.7 – 59.7 months) and 90% identified as Indigenous. 1722 child-months of observation were analysed (mean/child=8.58, 95%CI 8.18-9.0). The incidence of ARIwC was 24.8/100 child-months at risk (95%CI 22.3 – 27.5). Twenty-one children (10.5%) experienced recurrent ARIwC. Chronic cough was identified in 70/272 (25.7%) episodes of ARIwC. Predictors of recurrent ARIwC were presence of eczema, mold in the house, parent/carer employment status and having an Aboriginal and Torres Strait Islander mother/ non-Aboriginal and Torres Strait Islander father (compared to both parents being Aboriginal and Torres Strait Islander). Predictors of chronic cough included being aged <12 months, eczema, childcare attendance, previous history of cough >4 weeks duration, having an Aboriginal and Torres Strait Islander mother/ non-Aboriginal and Torres Strait Islander father (compared to both parents being Aboriginal and Torres Strait Islander) and a low income. Of those with chronic cough reviewed by a pediatric pulmonologist, a significant underlying disorder was found in 14 children (obstructive sleep apnoea = 1, bronchiectasis=2, pneumonia=2, asthma=3, tracheomalacia=6) Discussion This community of predominantly Aboriginal and Torres Strait Islander and socially disadvantaged children bear a considerable burden of ARIwC. One in 5 children will experience more than 3 episodes over a